Environmental health from global to local - Frumkin, Howard (San Francisco, CA Jossey-Bass, a Wiley brand, 2016)
"The bestselling environmental health text, with all new coverage of key topics Environmental Health: From Global to Local is a comprehensive introduction to the subject, and a contemporary, authoritative text for students of public health, environmental health, preventive medicine, community health, and environmental studies. Edited by the former director of the CDC's National Center for Environmental Health and current dean of the School of Public Health at the University of Washington, this book provides a multi-faceted view of the topic, and how it affects different regions, populations, and professions. In addition to traditional environmental health topics--air, water, chemical toxins, radiation, pest control--it offers remarkably broad, cross-cutting coverage, including such topics as building design, urban and regional planning, energy, transportation, disaster preparedness and response, climate change, and environmental psychology. This new third edition maintains its strong grounding in evidence, and has been revised for greater readability, with new coverage of ecology, sustainability, and vulnerable populations, with integrated coverage of policy issues, and with a more global focus. Environmental health is a critically important topic, and it reaches into fields as diverse as communications, technology, regulatory policy, medicine, and law. This book is a well-rounded guide that addresses the field's most pressing concerns, with a practical bent that takes the material beyond theory. Explore the cross-discipline manifestations of environmental health Understand the global ramifications of population and climate change Learn how environmental issues affect health and well-being closer to home Discover how different fields incorporate environmental health perspectives The first law of ecology reminds is that 'everything is connected to everything else.' Each piece of the system affects the whole, and the whole must sustain us all for the long term. Environmental Health lays out the facts, makes the connections, and demonstrates the importance of these crucial issues to human health and well-being, both on a global scale, and in our homes, workplaces, and neighborhoods"-- Provided by publisher.
"Environmental Health: From Global to Local, Third Edition by Howard Frumkin is a comprehensive and contemporary introductory core text for students in public health, preventive medicine, community health, other health sciences, and environmental health. Expert contributors discuss the major issues in environmental health: air, water, food safety, occupational health, radiation, chemical and physical hazards, environmental disasters, vector control, and environmental justice. Major changes to the third edition: - More global focus - New chapter on vulnerable populations, covering children, poor/minority communities, elderly, others - New chapter on sustainability - Shorten most chapters and eliminate redundancies throughout the book - Much more creative, engaging discussion questions "--Provided by publisher.
Includes bibliographical references and index.
Keywords: Environmental Health